1986
DOI: 10.1200/jco.1986.4.9.1295
|View full text |Cite
|
Sign up to set email alerts
|

Twenty years of MOPP therapy for Hodgkin's disease.

Abstract: The results of treatment of 198 patients with MOPP (mechlorethamine, vincristine, procarbazine, and prednisone) for Hodgkin's disease were analyzed after a median of 14 years of follow-up. Throughout the period of follow-up, 103 patients have remained continuously free of disease. Review of biopsy specimens of 43 patients originally classified as Hodgkin's disease, lymphocyte-depleted type, revealed that ten of these patients actually had diffuse immunoblastic or large cell non-Hodgkin's lymphomas. Of the 188 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
110
1
4

Year Published

1988
1988
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 408 publications
(119 citation statements)
references
References 27 publications
4
110
1
4
Order By: Relevance
“…Long-term survival was observed in approximately half of the patients treated with these regimens (Longo et al, 1986;Linch and Vaughan Hudson, 1988).…”
mentioning
confidence: 99%
“…Long-term survival was observed in approximately half of the patients treated with these regimens (Longo et al, 1986;Linch and Vaughan Hudson, 1988).…”
mentioning
confidence: 99%
“…The long-term outcomes of the MOPP regimen showed this to be an effective combination resulting in a progression free survival of 54% and an overall survival of 48% with 20 years of follow-up [4]. Although the MOPP chemotherapy regimen significantly changed the outcome of patients who previously had evidence of disease progression and subsequently died of disease, approximately one-third of patients treated with MOPP chemotherapy still had evidence of disease progression.…”
Section: Initial Chemotherapy Approachesmentioning
confidence: 99%
“…Neither performance status (Bakemeier et a., 1984;Jones et al, 1982) nor stage (DeVita et al, 1980;Bakemeier et al, 1984) have been of consistent significance in univariate analysis. In most reports sex has not been an independent prognostic factor, although Longo et al (1986) found that it contributed to the prediction of tumour related mortality when considered in combination with clinical liver involvement and pleural involvement. This factor was however significant previously (Wagstaff et al, 1986) This agreement in results reported in this analysis was not reached immediately.…”
Section: Methodsmentioning
confidence: 99%
“…Only DeVita et al (1980) found histological subtype to be important, patients E. = 47 with nodular sclerosing pathology having a significantly shorter survival than the rest. However, a recent review of these data (Kant et al, 1986;Longo et al, 1986) showed histology to no longer be of independent prognostic significance. Schilling et al (1982) found serum LDH to be (Wagstaff et al, 1986).…”
Section: Methodsmentioning
confidence: 99%